Políticas públicas en aplicación al derecho a la salud en las personas adultas mayores - Quito Illicachi, Tania Mishell (2025)
This research analyzes public policies related to the right to health for older adults, based on international instruments such as the International Covenant on Economic, Social, and Cultural Rights and the Ecuadorian Constitution. It focuses on evaluating the effectiveness of these policies in the Santo Domingo canton, highlighting their impact on priority and specialized care for this vulnerable group. The objective was to analyze the effectiveness of public policies concerning the health of older adults in Santo Domingo canton in 2024. The methodology employed a mixed approach. The qualitative approach allowed for the analysis of regulations, jurisprudence, and doctrines related to the right to health, while the quantitative approach was based on surveys and the application of a non-experimental and cross-sectional design, which enabled characterization of the problem and evaluation of policies. The results revealed inequalities in access to healthcare services, especially in rural areas, and a lack of knowledge about public policies among older adults. Additionally, weaknesses were identified, such as the limited implementation of effective mechanisms and the inadequate coverage of social security. The discussion highlights the need to strengthen inter-institutional coordination, allocate more resources, and foster the active participation of older adults in the formulation of public policies to prevent the violation of their constitutional rights. In conclusion, although there have been advancements, it is necessary to implement comprehensive strategies that ensure inclusion, specialized care, and the sustainability of the healthcare system to improve the quality of life for older adults.